2011
DOI: 10.1186/1743-7075-8-42
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol rich fraction supplementation improved lipid profile and oxidative status in healthy older adults: A randomized controlled study

Abstract: BackgroundVitamin E supplements containing tocotrienols are now being recommended for optimum health but its effects are scarcely known. The objective was to determine the effects of Tocotrienol Rich Fraction (TRF) supplementation on lipid profile and oxidative status in healthy older individuals at a dose of 160 mg/day for 6 months.MethodsSixty-two subjects were recruited from two age groups: 35-49 years (n = 31) and above 50 years (n = 31), and randomly assigned to receive either TRF or placebo capsules for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 57 publications
6
65
0
Order By: Relevance
“…In addition, a study on healthy elderly found that supplementation of tocotrienol-rich fraction (TRF) decreased deoxyribonucleic acid (DNA) damage [24]. The same improvement trend was observed in lipoprotein-lipid profile, with a reduction in markers of protein and lipid damage in the same study [25]. Furthermore, a finding shows that in ex vivo study using…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, a study on healthy elderly found that supplementation of tocotrienol-rich fraction (TRF) decreased deoxyribonucleic acid (DNA) damage [24]. The same improvement trend was observed in lipoprotein-lipid profile, with a reduction in markers of protein and lipid damage in the same study [25]. Furthermore, a finding shows that in ex vivo study using…”
Section: Introductionsupporting
confidence: 58%
“…lymphocytes showed the significant effect of TRF in reversing oxidative stress induced peroxiredoxin expression [22] and conferred protection against cell death [25].…”
Section: Asmara Et Almentioning
confidence: 99%
“…Whilst there is another study that reported a similar observation (Tan et al, 1991), most reported a neutral effect of tocotrienols on HDL levels (Baliarsingh et al, 2005;Mensink et al, 1999;Qureshi et al, 1995). Another study demonstrated that the same TTMF preparation was able to significantly increase plasma HDL after 6 months of treatment when compared to baseline levels (Chin et al, 2011). However, the same study showed that the HDL increment was only observed to be significantly 564…”
mentioning
confidence: 63%
“…In humans, we actually know that they significantly reduce LDL-cholesterolemia in diabetics [97] and improve HDL-cholesterol level and antioxidant status in healthy adults [98], but evidence of a direct vascular effect is still lacking.…”
Section: Dietary Antioxidantsmentioning
confidence: 99%